KAJIAN METODE DETEKSI DEGRADASI HUTAN MENGGUNAKAN CITRA SATELIT LANDSAT DI HUTAN LAHAN KERING TAMAN NASIONAL HALIMUN SALAK - Sigit Nugroho; I Nengah Surati Jaya; M. Buce Saleh; Antonius B Wijanarto (Jurnal Teknosains, 2011)
The study examined detection method of forest degradation using forest canopy density (FCD), maximum likelihood, fuzzy and belief dempster shafer classification method. Accuracy evaluation of classification and detection were based on overall accuracy which obtained from 51 ground sample plot. Canopy density, LAI, crown indicator, trees density and basal area (Lbds) were conducted   as field indicators. Accuracy of classification among forest density (trees/Ha) with four classification methods were FCD 61%, maximum likelihood 57%, fuzzy 51% and belief dempster shafer 49%. Based on temporal detection accuracy from 2003 until 2008, FCD had overall accuracy 68 %.  The result of research, FCD  is  the best method to detect of forest degradation.